Economic aspects of virtual water trade. (27th March 2017) - Oki, Taikan; Yano, Shinjiro; Hanasaki, Naota
Abstract: Although water is rarely traded over long distances by itself, the total weight of the water consumed to produce traded commodities exceeds the weight of any other commodity traded in the world. This concept is known as virtual water trade. Although space-/time-/commodity-based quantification has been conducted extensively, the underlying causes of this peculiar feature have thus far received little exploration. Here, we use estimates of water consumption from a global hydrological model and statistical data related to food trade to elucidate three facts that explain the fundamental nature of virtual water trade with respect to alleviating water scarcity. First, we quantitatively illustrate the unique position of water among commodities based on its unit price and quantity of sales. Water has an extremely low unit price, and a tremendous volume of water is consumed per person each day. Second, we show that rich but water-scarce countries tend to reduce local water consumption by importing virtual water. Third, we demonstrate that nations characterized by net virtual water exports have higher water resources and income per capita and that no countries fall below a certain threshold with respect to both GDP and water resources. These points suggest that the virtual water trade is explained by economic characteristics of water and that sustainable development depends on promoting the co-development of poverty alleviation and water resource development.